3D Mapping of the Submerged Crowie Barge Using Electrical Resistivity Tomography. (8th May 2018) - Simyrdanis, Kleanthis; Moffat, Ian; Papadopoulos, Nikos; Kowlessar, Jarrad; Bailey, Marian
Abstract : This study explores the applicability and effectiveness of electrical resistivity tomography (ERT) as a tool for the high-resolution mapping of submerged and buried shipwrecks in 3D. This approach was trialled through modelling and field studies of Crowie, a paddle steamer barge which sunk at anchor in the Murray River at Morgan, South Australia, in the late 1950s. The mainly metallic structure of the ship is easily recognisable in the ERT data and was mapped in 3D both subaqueously and beneath the sediment-water interface. The innovative and successful use of ERT in this case study demonstrates that 3D ERT can be used for the detailed mapping of submerged cultural material. It will be particularly useful where other geophysical and diver based mapping techniques may be inappropriate due to shallow water depths, poor visibility, or other constraints.